A note on Molluscan diversity and density of some fish ponds of Lalapatti Village Development Committee (VDC), Saptari district, Nepal - Subba, Bharat Raj; Kumar, Prakash; Adhikaree, Shaligram (Nepalese Journal of Biosciences, 2013)
Molluscan diversity of six fish ponds and a river of Lalapatti VDC, Saptari district was studied. In total, ten species of freshwater molluscs belonging to seven families and eight genera were recorded. Among them nine species were found in ponds and five species were recorded in the river samples. Maximum average density was recorded of Bellamya bengalensis (30.38/m2) and minimum for Corbicula alata (0.084/m2) DOI: http://dx.doi.org/10.3126/njbs.v1i0.7463 Nepalese Journal of Biosciences 1: 8-10 (2011)